Solvent screening and process optimization for high shear-assisted lipid extraction from wet cake of Nannochloropsis sp. (April 2020) - Kwak, Minsoo; Kim, Donghyun; Kim, Sungwhan; Lee, Hansol; Chang, Yong Keun
Abstract: Microalgae are regarded as a promising feedstock for biofuels and value-added products but still suffer from an inefficient lipid extraction process. In the present study, a simple and energy-efficient extraction method is demonstrated to extract oil directly from the wet cake (260 g/L) of Nannochloropsis sp. with an assist from the high shear mixer (HSM). After the initial solvent screening, the composition of co-solvent and operating conditions were optimized according to lipid composition and extraction yield. The high shear-assisted extraction process was found to achieve 83% lipid extraction yield (94% for EPA) in 5 min and 95% yield (100% for EPA) in 30 min with minimal amounts of solvents (0.9 ml hexane, 0.39 ml ethanol, and 0.057 ml sulfuric acid for 1 g of wet cell) at 8000 rpm, 55 °C. In comparison with various two-step wet extraction methods, the HSM offers the most economical extraction in terms of specific energy consumption of 1.38 MJ/kg dry cell. Therefore, the HSM can be considered as an attractive alternative to conventional extraction methods, providing a new paradigm of wet extraction for microalgae. Graphical abstract: Image 1 Highlights: High shear-assisted lipid extraction process was developed for Nannochloropsis sp. From solvent screening to process optimization was demonstrated. High lipid extraction yield and rate was achieved by high shear mixing. Hexane/ethanol/acid showed most efficient lipid extraction performance. 8000 rpm, 5 min of HSM treatment extract 83% of lipid and 95% of EPA.